Risks, Threats, and Challenges of Introducing Artificial Intelligence and Neural Network Algorithms into the Contemporary System of Socio-Political Communications: The Results of Expert Study - Sergey V. Volodenkov; Sergey N. Fedorchenko; Nikolai M. Pechenkin (RUDN Journal of Political Science, 2024)
In the context of global technological transformations and active penetration of artificial intelligence technologies and neural network algorithms into the digital space of socio-political communications, a new format of socio-political interactions is being formed today, defined by the widespread use of “smart” tools and mechanics of content generation and broadcasting in communication processes. In this regard, there is a demand for scientific research into the processes of the influence of artificial intelligence and neural networks on the content and functional parameters of modern socio-political communication interactions. The purpose of this study was to determine the relationship between “smart” technologies and the transformation of the contemporary space of sociopolitical communications in terms of the formation of risks, threats and challenges of a new type associated with the introduction of digital solutions based on the application of artificial intelligence technologies and neural network algorithms in the current practice of sociopolitical communications. The main research question is the extent and nature of the impact of the introduction of artificial intelligence technologies and neural network algorithms in the contemporary space of socio-political communications. To achieve the research goal and answer the research question, the authors applied the method of discourse analysis of scientific sources on the research topic, as well as conducted an international expert study, which allowed to identify key expert positions on the research topic and, based on the compilation of expert assessments, to identify the main risks, threats and challenges of socio-political nature formed in the processes of modern digital communications. The main conclusion of the paper is the thesis, substantiated and confirmed by the results of the research, that there is a wide range of socio-political risks, threats and challenges associated with the introduction of artificial intelligence technologies and neural network algorithms into the processes of contemporary digital communication. The paper provides a meaningful analysis of these risks, threats and challenges of a new type that can significantly affect the nature, dynamics and scenarios of the contemporary technological development of key spheres of life of the contemporary state and society.